Platform-as-a-Service (PaaS): Model and Security Issues - Devi T; Ganesan R (Institute of Advanced Engineering and Science, 2015)
Cloud computing is making a big revolution in the field of information technology thereby reducing capital expenditures spent. Computing is delivered as a service enabling effective utilization of computational resources. Certain security issues exist which prevents individuals and industries from using clouds despite its advantages. Resolving such problems may increase the usage of cloud thereby reducing the amount spent for resources. The paper focuses on one of the three service delivery models, Platform-as-a-Service(PaaS). PaaS model, layers in PaaS and PaaS providers are described along with the security issues encountered in PaaS clouds. The issues along with solutions discussed provide an insight into PaaS security for both providers and users which may help in future PaaS design and implementation.